2009
DOI: 10.4081/ijas.2009.s1.191
|View full text |Cite
|
Sign up to set email alerts
|

Welfare aspects in rabbit rearing and transport

Abstract: The review starts with the description of the rabbits' (Oryctolagus cuniculus) main habits and the current situation concerning the rabbit husbandry and management systems, as well as their effects on the welfare of these animals. As far as the intensive rabbit husbandry systems are concerned, the main problems are related to the time since rabbits have been domesticated and their adaptive capacity and coping styles as respects the farming environment and management systems. Both these aspects have implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 23 publications
0
52
0
2
Order By: Relevance
“…Thus lairage represents an additional period of deprivation of water and/or food. Usually, this area is placed outside, and very few abattoirs provide an enclosed area equipped with forced ventilation and water-misting sprays as a control strategy for adverse environmental conditions (Verga et al, 2009). In a survey of Spanish rabbit abattoirs (Buil et al, 2004), it was found that, before slaughter, there is a short lairage time where animals are kept in the same multi-floor transport cages in a holding area near the stunning facilities.…”
Section: Water and Feeding Interval Journey Times And Resting Periodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus lairage represents an additional period of deprivation of water and/or food. Usually, this area is placed outside, and very few abattoirs provide an enclosed area equipped with forced ventilation and water-misting sprays as a control strategy for adverse environmental conditions (Verga et al, 2009). In a survey of Spanish rabbit abattoirs (Buil et al, 2004), it was found that, before slaughter, there is a short lairage time where animals are kept in the same multi-floor transport cages in a holding area near the stunning facilities.…”
Section: Water and Feeding Interval Journey Times And Resting Periodsmentioning
confidence: 99%
“…In addition, plastic could reduce footpad injuries, although rabbits could chew plastic floors (TRAW, 2009). However, solid floors may impede ventilation and are more difficult to wash at the abattoir after slaughtering compared with those made of wire (Verga et al, 2009). …”
Section: Means Of Transportmentioning
confidence: 99%
See 3 more Smart Citations